Rapid Determination of Aesculin, Aesculetin and Fraxetin in Cortex Fraxini Extract Solutions Based on Ultraviolet Spectroscopy - Ming Yang; Jia-Lei Chen; Xiu-Feng Shi; Hui-Jue Niu (E-Journal of Chemistry)
To evaluate the application of ultraviolet spectroscopy for the rapid determination of aesculin, aesculetin and fraxetin in Cortex fraxini extract solutions, ultraviolet spectra of Cortex fraxini extract solutions from different batches were collected in the spectral range from 200 nm to 400 nm. The relationship between ultraviolet spectra and chemical parameters displayed some non-linear characteristics. Thus, K-OPLS was proposed to establish the calibration models for the determination of Cortex fraxini extract solutions between the reference data and ultraviolet spectra. The calibration results were achieved for the determination of Cortex fraxini extract solutions. The coefficients of determination in calibration (R2) for aesculin, aesculetin and fraxetin were 0.989, 0.957 and 0.939, while in prediction (R2) were 0.982, 0.979 and 0.962, respectively. And the root-mean-square error of prediction (RMSEP) for aesculin, aesculet and fraxetin were 11.99, 3.02 and 1.59 μg/mL. The results demonstrated that ultraviolet spectroscopy could be used for the rapid determination of these three components in Cortex fraxini extract solutions.